Pendampingan Pembelajaran Bahasa Inggris dengan Aplikasi Duolingo untuk Pelajar At-Tanzil Cheras, Malaysia - Zubaidi, Sujiat; Jiatrahman, Farisma; Ramadhan, M Akmal; Purnama, Hakim; Pahlevi, Miftah; Sasongko, Yogi Banar (Civiliza Publishing, 2025)
This research aims to analyze the effectiveness of English language learning assistance using the Duolingo application by students of the International Real Work (service) College at Darussalam Gontor University at At-Tanzil Students, Cheras, Malaysia. In this research, a qualitative approach was used in the form of a case study, with data collection carried out through observation techniques, interviews and document collection during the service period. The research results show that using the Duolingo application as a tool in the English learning process has a positive impact on students' motivation and mastery of English. This application allows students to learn independently and interactively, with various types of exercises tailored to their respective ability levels. Mentoring by service students also enriches the learning process by applying English language practices in the context of everyday life. These findings indicate that the integration of technology in language education can improve learning effectiveness and provide new opportunities in traditional teaching methods. This research provides insight for educational institutions in implementing digital technology as a support in the language learning process, especially in international service programs that involve cross-cultural interaction.